Three-Dimensional Impact Localization on Concrete Structures Using Novel Enhanced Cross-Correlation Algorithm and Designed Concrete Implantable Module - Chen, Qingjun; Yang, Ziqian; Li, Xiuquan; Sun, Xiangtao; Kong, Qingzhao (Frontiers in Materials, 2022)
Concrete structures are often subjected to undesirable impact loads. Impact localization in near real time is greatly essential for providing early warnings and evaluating impact load effects. In this article, a novel enhanced cross-correlation (ECC) algorithm enabled by a designed concrete implantable module (CIM) is proposed for precise prediction of the impact location on concrete structures. The stability of the ECC algorithm under the noise condition was numerically studied. The numerical results demonstrate that the proposed ECC algorithm has high adaptability in the low signal-to-noise ratio (SNR) condition compared with the traditional algorithm, which provides the possibility for employing this approach in real projects. In the experimental study, a series of impact tests on a concrete beam specimen were conducted to verify the accuracy of the proposed method for impact localization. The results indicate that the maximum and minimum distance errors between the real and predicted impact positions are 54.1 and 12.5 mm, respectively. Both the numerical and experimental studies demonstrate the feasibility of the proposed method for the prediction of impact locations.